Non-invasive wool hormone assessment of Australian merino rams (Ovis aries): a pilot investigation of cortisol and testosterone - Fox, Dylan; Wilson, Benn; Narayan, Edward (Frontiers in Veterinary Science, 2024)
Introduction Non-invasive hormone assessment is growing in interest as producers and livestock researchers seek new methods to assess animal welfare. Non-invasive wool assessment offers long-term, historic reflections of hormone concentration at the scale of weeks and months - and are not limited by sampling stress - thus making wool an appropriate tissue for long-term hormone analysis. This pilot study quantified cortisol and testosterone concentrations of ram fleece and determined if there is a significant difference between segments of the sample staple, and whether there is a correlation between hormones. Cortisol is a glucocorticoid produced within the adrenal glands and secreted in anticipation of or in response to a stressor. Testosterone is an androgen mainly synthesised within the testes of males and responsible for several critical functions including regulation of muscle growth, libido and spermatogenesis. Methods In our study, 70 topknot wool samples were collected from rams on a commercial stud property in Dirranbandi, Queensland, Australia. Of these animals, 12 samples were selected at random to undergo cortisol and testosterone quantification. In the laboratory, a single, intact staple was isolated from the total sample, divided into 10 mm segments and prepared for their respective (cortisol or testosterone) immunoassays. Results No significant difference (p > 0.05) was found between wool segments for either cortisol or testosterone, however, statistical differences (p < 0.05) were found between individuals for both hormones. A strong positive correlation (R2 = 0.9173, p < 0.05) was found between wool cortisol and testosterone concentrations. Discussion In summary, this study reveals the major future possibilities for non-invasive wool hormone assessment in merino rams.